The effect of nanochitosan hydrogel membrane on absorbtion of nickel, inhibition of Streptococcus mutans and Candida albicans - Andi Triawan; Pinandi Sri Pudyani; Soesatyo Marsetyawan HNE; Sismindari - (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: The use of fixed orthodontic appliance for a long time can potentially cause nickel ion release, increase in the growth of Streptococcus mutans (S. mutans) and Candida albicans (C. albicans). Chitosan has the ability to bind metal, antibacterial and antifungal. Physical modification of chitosan into the nanoparticles size will expand the surface of the chitosan so that the absorption of nickel ions and the inhibition of growth bacteria and fungi can be increased. Purpose: The purpose of the study was to determine the effect of nanochitosan hydrogel membrane to the absorption of nickel ions, and the inhibition of S. mutans and C. albicans growth. Methods: Nanochitosan hydrogel membrane with chitosan weight variation of 0.6; 0.8 and 1 g immersed in artificial saliva containing nickel 0.075 mg / L for 15, 30 and 45 minutes. The nanochitosan hydrogel membrane was tested for nickel ion absorption by Atomic Absorption Spectrophotometry, whereas the antibacterial and antifungal tests were done by exposing the nanochitosan hydrogel membrane - nickel on S. mutans and C. albicans in the wells of plate. Results: Demonstrated that absorption of nickel ions was related with the increase in weight of chitosan and soaking time. Inhibition of growth of S. mutans and C. albicans showed a positive correlation with the increase in weight of chitosan. Conclusion: Variation on chitosan weight on hydrogel membrane and variation on immersion time have effect on nickel ion absorption, inhibition of S. mutans and C. albicans growth.